Ramírez de Velasco basalts: New outcrops of basic rocks in the homonymous range, Santiago del Estero - Leal, P.R. (2010)
In this paper new basaltic outcrops from Ramírez de Velasco ranger (Santiago del Estero province) are described. They are basaltic dikes that vary from few meters to two kilometers long across the igneous basement. All these rocks show dark colors with aphyric (S9 sample) to porphyritic (S17 and S20 samples) textures. When these basalts present phenocrysts, they are composed of lagioclase within a groundmass of subophitic texture. The low alteration of the groundmass allows to recognise microliths of labradorite, augite and opaque minerals of about 0.2 and 0.5 mm. These sizes suggest a hypabisal emplacement of the biggest dikes. Sericite, chlorite, epidote, sphene and opaque minerals compose the alteration assemblage on these rocks. Quartz and carbonates mainly fill small cavities. The geochemical compositions of all analyzed samples support the petrographic classification. They have negative slopes of their trace elements and evidence affiliation with calc-alkaline basalts from magmatic arcs. Their similar textures, mineralogy and chemical compositions suggest that all these basalts where crystallized from the same source and due to the same magmatic process. On the basis of all these data and the features of the basalts that crops out in the surrounding of the study area, this volcanism is attributed to the post-orogenic stage of the Pampean orogeny and therefore it is correlated with the Balbuena Formation (Sierra Norte of Córdoba).